Keberadaan, Peran, Dan Tujuan Humas Kantor Wilayah Kementerian Agama Sumatera Utara Dalam Mendukung Komunikasi Dan Informasi Publik - Nurul Zannah; Dewi Triwulan; Meliastaras Surbakti; Hasan Sazali (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This research discusses the roles, strategies, and challenges faced by the Public Relations (PR) division of the Regional Office of the Ministry of Religious Affairs of North Sumatra in supporting public communication. PR serves as a bridge between the government and the public but faces constraints due to limited human resources and budget. The use of social media and collaboration with mass media have been well implemented. However, strengthening PR teams in regional areas and optimizing digital technology are recommended to enhance the effectiveness of information dissemination and increase public awareness of religious moderation.